To Build as Well as Destroy American Nation Building in South Vietnam - Andrew, Gawthorpe (Cornell University Press, 2018)
This book provides the most detailed analysis yet of the failure of U.S. nation-building in the Vietnam War. In doing so, it demolishes the "better war" school of writing on the topic, which argues that the U.S. was successful in building a legitimate and viable non-Communist state in South Vietnam in the latter years of the war. Drawing on fresh archival collections and previously unseen oral histories with dozens of U.S. nation-builders, the book demonstrates that the U.S. never came close to achieving victory. The book's narrative stretches from the offices in Washington in which policy was designed down into the villages in which it was implemented, providing the most comprehensive analysis yet of the largest and best-resourced nation-building program in U.S. history. Only by understanding and facing the reasons for this failure can we avoid repeating the tragic mistake of the Vietnam War again in the future.